2010
DOI: 10.5694/j.1326-5377.2010.tb03949.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic suppurative lung disease and bronchiectasis in children and adults in Australia and New Zealand. A position statement from the Thoracic Society of Australia and New Zealand and the Australian Lung Foundation

Abstract: Consensus recommendations for managing chronic suppurative lung disease (CSLD) and bronchiectasis, based on systematic reviews, were developed for Australian and New Zealand children and adults during a multidisciplinary workshop. The diagnosis of bronchiectasis requires a high‐resolution computed tomography scan of the chest. People with symptoms of bronchiectasis, but non‐diagnostic scans, have CSLD, which may progress to radiological bronchiectasis. CSLD/bronchiectasis is suspected when chronic wet cough pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 117 publications
(34 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…The marked paucity of RCTs [21,55] is reflected in the existence of only a single (small) published placebo-controlled RCT in children with bronchiectasis [21,56]. That study described a reduction in sputum purulence and airway hyper-responsiveness in children receiving roxithromycin (n = 13) [57].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The marked paucity of RCTs [21,55] is reflected in the existence of only a single (small) published placebo-controlled RCT in children with bronchiectasis [21,56]. That study described a reduction in sputum purulence and airway hyper-responsiveness in children receiving roxithromycin (n = 13) [57].…”
Section: Discussionmentioning
confidence: 99%
“…There are no RCTs on the management of bronchiectasis exacerbations in children [58]. Almost all current recommendations are based on CF management [21,28]. Such extrapolation can, on occasions, be detrimental for those with non-CF bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cohort data have shown that about 80% of newly diagnosed adults (non-smokers) with bronchiectasis reported symptoms dating back to childhood, and that the duration of chronic cough (the most common symptom of bronchiectasis [24]) was related (r = −0.51, P <0.001 in non-smokers) to lung function at diagnosis [25]. Arguably, appropriate overall management and treatment of exacerbations (leading to a reduction in persistent symptoms) potentially prevents or reduces deterioration of chronic respiratory disease [26].…”
Section: Introductionmentioning
confidence: 99%